COVID-19 impacts medical journal submissions (2020)
The public health crisis of the COVID-19 pandemic critically shifted the infrastructure of the global health care system (Lai et al., 2020). The current pandemic has also resulted in an increase in the number of COVID publications. Indeed, we observed an increase in Pubmed searches performed on June 12th compared to July 18th (21,751 vs 32,963 respectively). This finding is consistent with previous literature reports highlighting the increase in publications in the midst of pandemics (Zhang et al., 2020). Correspondingly, one author (SEJ) noted a significant increase in review requests received for non-COVID related articles, between March 25 and May 1, 2020, which prompted the query as to whether this was due to an increase in reviewers declining to review or an increase in submissions.